Big boots to fill—the next generation continuing differently. (May 2016) - Clinton, Eric; Craig, Justin B.; Diaz-Moriana, Vanessa; Faherty, Catherine M.
This case history describes the challenge facing Carlos García, the third-generation successor of a Spanish family business, as he takes over the reins of Hispalis and prepares to continue the business 'differently'. In two generations, Hispalis has morphed into a global conglomerate, with a portfolio of business ventures in multiple industries and countries. The case history facilitates discussion of business and family issues and is appropriate for beginning-level undergraduate students in the areas of entrepreneurial leadership, family business, strategic management and corporate governance.